2019
DOI: 10.11113/sh.v11n2-2.1652
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Supervisor Safety, Safety Management Practices, and Safety Compliance Behaviour among Employees

Abstract: This cross-sectional research was conducted to establish the relationship between supervisor safety, safety management practices, and safety compliance behaviour among medical laboratory personnel in the private sector. There were 119 respondents from private medical laboratories in Selangor. The data were collected using a survey questionnaire adopted from past research that measured supervisor safety, safety management practices, and safety compliance behaviour. The data obtained from the study were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Third, by understanding the differences in safety leadership and supervisor safety management and their simultaneous effect on safety performance, the owner/managers of logistics companies can develop effective action plans to enhance their companies' safety performance and reduce the accidents. However, this study findings stated that the role of the owner-manager is vital in long-term safety success and safety concern, and safety motivation inspire workers to succeed in safety performance [32].…”
Section: Managerial Implicationsmentioning
confidence: 64%
See 1 more Smart Citation
“…Third, by understanding the differences in safety leadership and supervisor safety management and their simultaneous effect on safety performance, the owner/managers of logistics companies can develop effective action plans to enhance their companies' safety performance and reduce the accidents. However, this study findings stated that the role of the owner-manager is vital in long-term safety success and safety concern, and safety motivation inspire workers to succeed in safety performance [32].…”
Section: Managerial Implicationsmentioning
confidence: 64%
“…The purpose of this research is to investigate how safety management techniques improve safety performance. More specifically, the logistics companies working to enhance their workplace safety and control the accidents rations actively [31,32]. In this regard, the current research is to investigate that how safety leadership and supervisor roles can affect positively the safety performance (behavior safety) in logistics sector of Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…The number of accidents and injuries resulting from breaching safety policies is likely to be reduced by a higher degree of safety rules enforcement. Significant factors contributing to positive safety compliance behaviour were management commitment, security coordination, safety control, efficient safety instruction, safety laws and regulations, safety management system, an incentive for safety, safety, health officers, and personal protective equipment (Hassan, 2019). Safety compliance was the factor reflecting safety behaviour in outdoor participation.…”
Section: Sb and Outdoor Participantsmentioning
confidence: 99%
“…For instance, research conducted in Scandinavian countries revealed that a positive safety climate was linked to reduced injury rates and improved safety performance (15). Similarly, an Indian study found that a robust supervisor-worker relationship, contributing to a positive safety climate, resulted in improved safety performance (13). These findings emphasize that a favorable safety climate plays a pivotal role in establishing a secure work environment and averting occupational mishaps (15).…”
Section: Introductionmentioning
confidence: 99%
“…Safety climate, a gauge of an organization's safety culture, wields considerable influence over occupational safety and health (OSH) outcomes (12). Vinodkumar and Bhasi (2009) introduced a safety climate tool, specifically a safety climate questionnaire, designed to evaluate safety climate within organizations (12,13,14). This instrument aims to capture employees' perceptions regarding safetyrelated elements like management's dedication to safety, supervisor safety practices, and coworker safety conduct (12,13).…”
Section: Introductionmentioning
confidence: 99%